Ethno-Religious Conflict and the Quest for Peace in a Plural Society in Africa - Kemi Anthony Emina (Britain International for Academic Research (BIAR) Publisher, 2020)
This article examines the elusive search for peace in a plural Society in Africa, amid persistent ethno-religious conflicts and violent attacks in eminent. The central thesis of this article focused on why existing theoretical perspectives on the nature and management of ethnoreligious conflicts in Africa have disappointed expectations, and what is required to achieve peace among plural African societies. This article used Nigeria as a case study. The research argues that conflict resolution has an ontological dimension and that achieving peace in plural societies requires a process of genuine orientation that reworks the human consciousness to accept the inevitability of the 'Other' both to the self and its aspirations for survival. This research employs the method of textual and critical analysis in carrying out this research.